1998
DOI: 10.1175/1520-0485(1998)028<1624:ansotc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A New Second-Order Turbulence Closure Scheme for Modeling the Oceanic Mixed Layer

Abstract: A new second-order turbulence closure scheme is proposed for the oceanic mixed layer. The scheme is similar in complexity to a Mellor-Yamada level 2.5 scheme in that the turbulent kinetic energy is the only turbulence quantity treated prognostically with the others determined diagnostically. The main difference lies in the treatment of the turbulent fluxes. While momentum fluxes are assumed to be downgradient, the other turbulent fluxes allow for nonlocal and countergradient contributions. The model was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…Other studies investigated second-moment turbulence closure models by including the CL vortex force in the TKE equation (D'Alessio et al 1998), the dissipation length scale (Kantha and Clayson 2004), and the stability functions (Harcourt 2013(Harcourt , 2015. The additional turbulent flux down the gradient of the Stokes drift is a key component to the modifications presented by Harcourt (2013Harcourt ( , 2015.…”
Section: Geophysical Turbulence Closure Modelsmentioning
confidence: 99%
“…Other studies investigated second-moment turbulence closure models by including the CL vortex force in the TKE equation (D'Alessio et al 1998), the dissipation length scale (Kantha and Clayson 2004), and the stability functions (Harcourt 2013(Harcourt , 2015. The additional turbulent flux down the gradient of the Stokes drift is a key component to the modifications presented by Harcourt (2013Harcourt ( , 2015.…”
Section: Geophysical Turbulence Closure Modelsmentioning
confidence: 99%
“…A fourth-order low-pass Butterworth filter with a 6 h cutoff period was deployed twice, once forward and once backward, to minimise phase distortion for the measurement errors and high-frequency motion, following Mitchell et al (2005), Jarosz et al (2007) and Teague et al (2007). vertically upwards, and assuming the flow is homogeneous in the horizontal, the rotational hydrodynamic equation and temperature equation can be written as (D'Alessio et al, 1998): where u and v are the velocity components with respect to the x and y directions, θ is potential temperature, K M is eddy viscosity, K H is eddy diffusivity, f is the Coriolis parameter, Q SR is solar shortwave radiation, ρ w is water density and c pw is water heat capacity at constant pressure.…”
Section: Typhoon Megi and Observational Datamentioning
confidence: 99%
“…In our study, MESO-NH is coupled to a one-dimensional ocean model (Gaspar et al, 1990) that has been shown to represent relatively well the vertical mixed layer structure and the SST evolution (Blanke and Delecluse, 1993;Alexander et al, 2000). Several ocean turbulence models are based on the Gaspar et al (1990) model equations (D'Alessio et al, 1998;Giordani et al, 2006). Using this air-sea coupled modelling system, the aim of the present article is to examine the ocean response to the high-resolution atmospheric forcing imposed during Mediterranean heavy precipitation events.…”
Section: Introductionmentioning
confidence: 99%